Observation of a new [xi]-b resonance - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Gerick, David; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; Khanji, Basem; Leverington, Blake; et al. (Physical review letters, 2018)
From samples of pp collision data collected by the LHCb experiment at √s=7, 8 and 13 TeV, corresponding to integrated luminosities of 1.0, 2.0 and 1.5 fb−1, respectively, a peak in both the Λ0bK− and Ξ0bπ− invariant mass spectra is observed. In the quark model, radially and orbitally excited Ξ−b resonances with quark content bds are expected. Referring to this peak as Ξb(6227)−, the mass and natural width are measured to be mΞb(6227)−=6226.9±2.0±0.3±0.2 MeV/c2 and ΓΞb(6227)−=18.1±5.4±1.8 MeV/c2, where the first uncertainty is statistical, the second is systematic, and the third, on mΞb(6227)−, is due to the knowledge of the Λ0b baryon mass. Relative production rates of the Ξb(6227)−→Λ0bK− and Ξb(6227)−→Ξ0bπ− decays are also reported.